2022
DOI: 10.1007/s11357-022-00559-7
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol induces autophagy and improves neuronal health associated with SIRT1 mediated longevity

Abstract: Autophagy is a catabolic process to eliminate defective cellular molecules via lysosome-mediated degradation. Dysfunctional autophagy is associated with accelerated aging, whereas stimulation of autophagy could have potent anti-aging effects. We report that cannabidiol (CBD), a natural compound from Cannabis sativa, extends lifespan and rescues age-associated physiological declines in C. elegans. CBD promoted autophagic flux in nerve-ring neurons visualized by a tandem-tagged LGG-1 reporter during aging in C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Thus, early-life induction of TLs might help to attenuate the autophagic load at older ages by providing robust autophagic turnover throughout life. Accordingly, continuous autophagy stimulation by other approaches has been shown to extend lifespan and healthspan in various species (Carmona-Gutierrez et al, 2019; Ogasawara et al, 2020; Wang et al, 2022). Remarkably, even short-term rapamycin administration in young individuals results in prolonged autophagy activation that suppresses age-related pathologies in the gut (Juricic et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, early-life induction of TLs might help to attenuate the autophagic load at older ages by providing robust autophagic turnover throughout life. Accordingly, continuous autophagy stimulation by other approaches has been shown to extend lifespan and healthspan in various species (Carmona-Gutierrez et al, 2019; Ogasawara et al, 2020; Wang et al, 2022). Remarkably, even short-term rapamycin administration in young individuals results in prolonged autophagy activation that suppresses age-related pathologies in the gut (Juricic et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that DMSO-induced oxidative stress is accompanied by the inhibition of SIRT3 and SOD2 and that LnHS prevented the downregulation of both enzymes induced by DMSO. Previously, a modulation of SIRT proteins had been highlighted but only by phytocannabinoids and never by the lignamide fraction ( Gerasymchuck et al, 2022 ; Wang et al, 2022 ). Similarly, the effects of hemp extracts on the modulation of IL-8 have been found for phytocannabinoids but not considering different extracts and cellular models such as lung epithelial cells, macrophages, and human keratinocytes ( Anil et al, 2021 ; Suryavanshi et al, 2022 ; Tortolani et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oxidative stress, mitochondrial malfunction seems also to be implicated in DMSO detrimental effects; sirtuins are the main regulators of mitochondrial stress response ( Yuan et al, 2014 ). The sirtuin family comprises a group of highly conserved nicotinamide adenine dinucleotide (NAD+)-dependent protein deacetylases, consisting of seven species in mammals, known as sirtuin 1–7 (SIRT1-7) ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cannabidiol, a natural compound from Cannabis sativa L. (Cannabaceae) extended lifespan and improved neuronal health in C. elegans by induction of autophagy (Ref. 226).
Figure 5.Autophagy-related pathways regulated by natural compounds in neurological aging (Figure created with Biorender.com).
…”
Section: Natural Active Compounds In Longevity Interventionmentioning
confidence: 99%